Does metabolic stress affect the decrease in oxygen uptake at the end of all-out exercise - Thomas, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The present study investigated the effects of altering extracellular buffer capacity during acute all-out exercise on VO2 decrease. Although some previous studies have investigated the effects of prealkalosis on VO2 kinetics during submaximal and supramaximal exhaustive exercises with controversial effects, we hypothesised that the VO2 decrease at the end of supramaximal exercise performed until exhaustion could be affected by acidosis, and we further posited that preexercise-induced alkalosis could prevent the VO2 decrease. Methods: We investigated the oxygen uptake response and performance during 70-s all-out exercise performed in two conditions, preexercise alkalosis (BIC : 0,3 g/kg NaHCO3-) and placebo (PLA : 0.2 g/kg CaCO3) in highly-trained subjects. Exercise tests were conducted using an electronically braked cycle ergometer (Excalibur Sport, Lode, Groningen, The Netherlands). Blood samples were collected at rest, before the test and at 0, 5 and 8 min of 70-s exercise recovery (i-STAT, Abbott, Les Ulis, France). Results: Significant differences between PLA and BIC are observed for power output during the last 50s (P < 0.05) and total power output (P < 0.01). Oxygen uptake response increase to a steady state corresponding to 95.2 ± 3.2 and 99.7 ± 2.8 % of VO2max for PLA and BIC respectively, before to significantly decrease of 9.2 ± 3.2 for PLA and 7.8 ± 1.9 % for BIC with no significant difference among groups. Discussion: The results suggests that the decrease in VO2 at the end of supramaximal exercise of 70 s can not be explained by middle acidosis (pH=7.13±0.01 in PLA vs 7.22±0.01 in BIC) since VO2 decrease was also observed in alkalosis condition. As VO2 decrease was related to a decrease in Ventilation in Pla group (r=0.71, P<0.01), muscle respiratory fatigue could be involved in this phenomenon. Indeed, subjects who presented higher VO2 decrease are those with higher ventilation decrease in both conditions, but they did not present a decrease in arterial oxygen saturation comapred to other subjects. If ventilatory muscle fatigue could be an important factor contributing to VO2 decrease, others additional factors could be involved to explain this phenomenon, but not metabolic stress.